2014
DOI: 10.1039/c4cs00185k
|View full text |Cite
|
Sign up to set email alerts
|

Jack of all trades: versatile catechol crosslinking mechanisms

Abstract: Catechols play an important role in many natural systems. They are known to readily interact with both organic (e.g., amino acids) and inorganic (e.g., metal ions, metal oxides) compounds, thereby providing a powerful system for protein curing. Catechol crosslinked protein networks, such as sclerotized cuticle and byssal threads of the mussel, have been shown to exhibit excellent mechanical properties. A lot of effort has been devoted to mimicking the natural proteins using synthetic catechol-functionalized po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
614
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 593 publications
(632 citation statements)
references
References 150 publications
(229 reference statements)
15
614
1
2
Order By: Relevance
“…However, many of the crosslinking mechanisms for catechol-containing polymers that have been proposed involve the reaction between a quinone-intermediate and another amino acid. Amino acids that have been variously proposed to be involved in Table III. intermolecular and intramolecular crosslinking reactions include lysine, histidine, cysteine and DOPA; the results from the present work indicate that cross-linking the protein resulted in an increase of the corrosion inhibition of the HY80 substrate, therefore the protein may not require a large amount of DOPA in its composition to crosslink effectively; 15 the observations from the present work support those findings.…”
Section: Resultssupporting
confidence: 82%
“…However, many of the crosslinking mechanisms for catechol-containing polymers that have been proposed involve the reaction between a quinone-intermediate and another amino acid. Amino acids that have been variously proposed to be involved in Table III. intermolecular and intramolecular crosslinking reactions include lysine, histidine, cysteine and DOPA; the results from the present work indicate that cross-linking the protein resulted in an increase of the corrosion inhibition of the HY80 substrate, therefore the protein may not require a large amount of DOPA in its composition to crosslink effectively; 15 the observations from the present work support those findings.…”
Section: Resultssupporting
confidence: 82%
“…Consistent with the suggestion of oxidative crosslinking at the developing interface, recent studies of adult barnacle interfaces using in situ cyclic voltammetry have revealed electrochemical behavior consistent with the presence of redox active compounds (Golden et al, 2016), as well as spectroscopic evidence for the presence of phenolic compounds in interfacial barnacle fluids (Burden et al, 2012). Quinone tanning can be driven by free radicals or enzymes and mediates crosslinking in diverse systems and contexts, including sclerotized insect cuticle and mussel byssal threads (Korytowski et al, 1987;Waite, 1995;Suderman et al, 2006;Yang et al, 2014). Surprisingly, antimicrobial properties of barnacle secretions have not been deeply explored, even after the identification of a barnacle cement protein with homology to the antibacterial enzyme lysozyme (Kamino and Shizuri, 1998).…”
Section: Discussionmentioning
confidence: 55%
“…We suggestt hat the coupling reactiono ft hiols catalyzed by PDA should follow am echanism similar to that of mussel adhesion [4,5] and that of disulfide bond formation in DsbB [23,24] in nature.S cheme 1s hows that the proposed mechanism consists of three steps:o ne, nucleophilic attack of the quinone groups on the PDA particles (state 1) by the first thiolate anion to form at hiol-dopamine adduct (state 2), as illustrated by previousw ork; [38] two, attack of the thioether adduct by as econd thiolate anion to form ad isulfide and phenol-state dopamine (state 3);t hree, oxidization of phenol-state dopamine into quinone-state dopamine by oxygen dissolved in the solution.The quinone groups on the PDA particles were identified by X-ray photoelectrons pectroscopy (XPS) (FigureS4), which is in accordance with the previousr eport. [39] To further understand this mechanism, PDA particlesw ereu sed to sequentially catalyzet he individual oxidative couplings of sodium 3-mercapto-1-propanesulfonate (MPS), MGL, and sodium 3-mercapto-1-propanesulfonate (shown in Figure 1).…”
mentioning
confidence: 88%
“…[1][2][3][4][5][6] They playacrucial role in maintaining the conformationals tability and biological activity of proteins [1,2] and participate in the adhesion process of mussel foot protein. [4,5] Over the past decades, these chemicals have received much attentiona saresult of their artificial applicationsi ns ynthesizing pharmaceutical molecules, [7,8] constructing functional materials, [9][10][11] building dynamic combinatorial libraries, [12,13] and preparing sulfur-containing organic compounds. [14,15] Numerous methods have been developed to form disulfide bonds in both scientific laboratories and industrial factories.…”
mentioning
confidence: 99%
See 1 more Smart Citation